Morphological diversity and dna polymorphism of common oat (Avena sativa L.) landraces cultivated in Poland. - Nowosielska, Dorota; Nowosielski, Jarosław (Plant Breeding and Seed Science, 2008)
The aim of the work was characterization of morphological diversity and DNA polymorphism of common oat landraces. 25 Morphological traits and DNA polymorphism have been examined using AFLP methods. It has been found, that identification of oat landraces is possible based on the examined morphological traits. The examined accessions were differentiated by traits important for intraspecific taxonomy of oat: type of panicle, presence of awns, colour of grain, as well as other morphological traits, such as shape of panicle, rigidity of stem leaves, and type of awns. Relationships of morphological traits of leaves, grains, and stem with some DNA fragments suggesting presence of molecular markers of these morphological traits have been found. Morphological similarity of landraces doesn’t correspond to affinity complied with DNA similarity of these objects...